Steering Control System Design on Electric Car using Remote Control - Adri Tamma Furqon; Angga Rusdinar; Azam Zamhuri Fuadi; Martin Hardiyanto; Usman Sakiman (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2021)
Teleoperation vehicles such as Unmanned Ground Vehicles can be used for surveillance or exploration, including the detection of mines. PT. Pindad plans to develop a vehicle for minesweeping. In this research, a prototype of an unmanned vehicle system was built. The vehicle had a steering system that can be remotely controlled, which allows for more maneuverability. A Proportional Integrated and Derivative control was attached to the system. The PID control has the ability to speed up and generate system responses according to user requirements. The experiment result showed that the system got a rise time response of 1.6 seconds and a steady state error of 0%, and the percentage comparison between the angle given by the remote control and the angle read by the rotary encoder is 97.89 %.